2022
DOI: 10.1039/d1tb02746h
|View full text |Cite
|
Sign up to set email alerts
|

Towards a protein-selective Raman enhancement by a glycopolymer-based composite surface

Abstract: Surface-enhanced Raman scattering (SERS), which is based on the surface plasmons resonance (LSPR) of noble metal nanostructures, is widely used in biological field due to its advantages of non-damaging samples...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…This platform demonstrated specific adsorption of target proteins and selective Raman enhancement ability (Figure 2C). 31 Apart from metal‐based substrates, some 2D materials have also been explored as SERS substrates based on the chemical enhancement mechanism 32 …”
Section: Optical Sensing Mechanisms and Sensor Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This platform demonstrated specific adsorption of target proteins and selective Raman enhancement ability (Figure 2C). 31 Apart from metal‐based substrates, some 2D materials have also been explored as SERS substrates based on the chemical enhancement mechanism 32 …”
Section: Optical Sensing Mechanisms and Sensor Materialsmentioning
confidence: 99%
“…(C) Construction of the polymer‐AgNPs composite SERS substrate. Reproduced with permission 31 . Copyright 2022, The Royal Society of Chemistry.…”
Section: Optical Sensing Mechanisms and Sensor Materialsmentioning
confidence: 99%
“…42 Chen et al prepared methacryl amide monomer 9b from glucosamine hydrochloride and methacryloyl chloride under the same conditions. [43][44][45][46][47][48] Becer et al reported D-mannose acryl amide monomer 10, 2-(D-mannosyloxy)hydroxyethyl acrylamide, which was synthesized from D-mannose pentaacetate and N-hydroxyethyl acryl amide in the presence of BF 3 •Et 2 O and subsequent deprotection. [49][50][51] Tanaka et al synthesized a series of acryl amide monomers with various triazole-linked sugar groups, such as lactose, 6′-sialyllactose, sialyl N-linked oligosaccharide and maltose.…”
Section: Reviewmentioning
confidence: 99%
“…Random copolymers, reported by Chen et al, can be obtained when monomers with similar reactivity are added simultaneously. [44][45][46][47]89 For example, in 2019, they reported the random copolymer from hydrophilic 9a, positively charged N-(3-(dimethylamino)propyl)methacrylamide as the monomer and hydrophobic N,N-diethylmethacrylamide by RAFT polymerization at room temperature using simulated sunlight as the initiator source. 46 The turbidimetry results showed that the bacterial adhesion capacity of the polymer was elevated with an increase of the cationic and hydrophobic components.…”
Section: Reviewmentioning
confidence: 99%
“…[114] Chen et al created hybrid SERS substrates by combining glycopolymers with in situ-produced Ag nanoparticles, displaying targeted adsorption of proteins and selective Raman amplification with minimum detection value of 10 À 7 mg/ml . [115] In another study, a microfluidic system was created to maximize interactions among saliva specimens and a SERS substrate based on suspended Ag nanoparticles to enable quick drug detection at biologically relevant concentrations. [116] They reported presence of methamphetamine in the sample at a concentration of 10 nM, which is well below physiological value.…”
Section: Optical Sensingmentioning
confidence: 99%